Advances in screening methods and breeding for resistance to downy mildew and stem borers in maize - Kling, J.G.; Cardwell, K.F.; Bosque Pérez, N.A.; Kim, S.K. (1997)
Maize is the most important cereal in sub-Saharan Africa. It is relatively inexpensive and provides many families with much-needed nutrients. For the farmers, it matures early and Is a source of ready income. Maize production Is being threatened by some diseases and pests, among which are downy mildew and stem borers. Serious yield losses often occur. This paper summarizes two studies that report the efforts of liT A scientists to screen and breed maize varieties for resistance to downy mildew and stem borers.